THE ROLE OF HUMAN CAPITAL READINESS, JOB CRAFTING, AND INNOVATIVE MINDSET ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AMONG EMPLOYEES OF PT PLN (PERSERO) UP3 TANJUNG KARANG - Audi Ocha Deamelinda; Euis Mufahamah; Harold Kevin Alfredo (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the effect of Human Capital Readiness, Job Crafting, and Innovative Mindset on the Organizational Citizenship Behavior (OCB) of employees at PT PLN (Persero) UP3 Tanjung Karang. In the context of a highly regulated public utility sector undergoing digital transformation, fostering voluntary extra-role behavior is crucial for organizational success. A quantitative approach with a causal explanatory design was employed, utilizing a sample of 115 employees selected through simple random sampling. Primary data was collected using a structured questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results reveal that Human Capital Readiness and an Innovative Mindset have a positive and significant effect on OCB, with the Innovative Mindset acting as the most dominant driver. Conversely, Job Crafting does not have a significant effect on OCB, which is likely due to the highly procedural nature and strict operational standards of the work environment. Simultaneously, the three independent variables account for 76.7% of the variance in OCB. These findings suggest that to enhance extra-role behaviors, management should focus on improving employee technical and psychological competencies while actively fostering a creative and innovative work culture.